Do municipal factors influence the type of schooling newly arrived refugees receive? - Will, Gisela [Verfasser]; Becker, Regina [Verfasser] (My University, 2025)
„In the context of refugee immigration in the mid‐2010s, a considerable number of adolescents of compulsory school age came to Germany. This group of lateral entrants to the German school system is more frequently enrolled in less demanding school types and often taught in separate classes. Previous research suggests that, in addition to individual and family‐related factors, educational policy regulations at the federal‐state level impact the schooling of refugees. However, these regulations are relatively abstract, leaving the individual municipalities considerable room for implementation. Furthermore, the associated administrative regulations can vary greatly between districts and might affect school integration differently. Yet, the influence that such municipal‐level factors have on refugees’ educational participation has hardly been quantitatively researched. We analyse whether conditions at the municipal level correlate with the school type and class type attended by refugees. We expect education‐related municipal resources, but also local experience with immigrants, to be important. Applying multivariate multilevel models, we test these assumptions with data from the ReGES study regarding 1,879 adolescent refugees. The results show that the more refugee pupils there are in the municipality, the more likely it is that pupils will be educated in a separate class for newcomers. In most cases, examining the further hypotheses shows the assumed direction of the relationships, but they are not statistically significant. Overall, municipal factors only contribute to a very small extent to explaining the schooling of lateral entrants in our analyses. Possible explanations for this are discussed in the conclusion.“ (authors’ abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; 370; Flüchtling; Ausländischer Jugendlicher; Schulpflicht; Rechtliche Regelungen; Bundesländer; Gemeinde[Kommune]